How Could Emergency Modify our Normal Ethics Standards? A Brief Review of Selected Chapters in Emergency Ethics - St-Denis, Karine (BioéthiqueOnline, 2015)
This review is about Emergency Ethics, the first in the four-volume series Emergency Ethics, Law and Policy. It analyses chapters addressing the question: How could emergency modify our normal ethics standards? The chapters offer three angles on the question: conceptual analysis, empirical analysis and case study.